Perbandingan Nilai Ujian Nasional dan Ujian Sekolah Mata Pelajaran Matematika SMA Program IPA Tahun Pelajaran 2010/2011 - Fahmi -- (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this research is to compare the scores of National Exam and the scores from schools and also to identify the characteristics of Mathematics items for Senior High Schools at IPA programme. The analysis is conducted using Iteman and Bigsteps Software. The procedures of test callibration between zone is using Model Rasch Theory (1-parameter) with the Bigsteps, Iteman, dan Microsoft Excel softwares. The sampling methode is stratified Random sampling. The number of students to be a sample is 20.000. The test reliability for West zone is 0,837, Center zone is 0,862, and East zone is 0,840. Based on classical test theory, the Mathematics test difficulty for West zone is 0,786, Center zone is 0,739, East zone is 0,757. The highest mean of Mathematics schools score is in Province of Bali (8,63) and the lowest is in Province of Kalimantan Barat (7,60). The highest mean of Mathematics National Exam Score is in Province of Bali (9,11) and the lowest is in Province of Sumatera Barat (7,23). The highest mean of final Mathematics score is in Province of Bali (8,92) and the lowest is in Province of Nusa Tenggara Timur (7,03). The highest difference between schools scores and the National Exam scores is in Province of DI Yogyakarta, that is 1,81 point and the lowest diffence is in Province of Banten, that is 0,01 point.Â ABSTRAKTujuan dari penelitian ini yaitu untuk membandingkan nilai Ujian Nasional (UN) dan nilai sekolah (NS) serta mengetahui karakteristik butir soal Matematika SMA program IPA. Analisis dilakukan menggunakan software Iteman dan Bigsteps. Penyetaraan paket tes antar zone menggunakan teori Rasch Model (satu parameter) dengan bantuan software Bigsteps, Iteman, dan Microsoft Excel. Teknik pengambilan sampel dalam penelitian ini menggunakan cara stratified Random sampling dan jumlah siswa yang menjadi sampel 20.000 siswa. Hasil analisis Reliabilitas tes untuk Zone Barat menunjukkan 0,837, zone Tengah 0,862, dan zone Timur 0,840. Berdasarkan teori klasikal tingkat kesukaran paket tes Matematika Zone Barat 0,786, zone Tengah 0,739, zone Timur 0,757. Nilai rata-rata sekolah (NS) Matematika tertinggi Provinsi Bali (8,63) dan nilai rata-rata terendah Provinsi Kalimantan Barat (7,60). Nilai rata-rata UN Matematika tertinggi Bali (9,11) dan nilai rata-rata terendah Provinsi Sumatera Barat (7,23). Nilai rata-rata NA Matematika tertinggi Provinsi Bali (8,92) dan nilai rata-rata terendah Provinsi Nusa Tenggara Timur (7,03). Selisih antara NS dan UN terbesar Provinsi DI Yogyakarta yaitu 1,81 poin dan selisih terendah adalah Provinsi Banten yaitu 0,01 poin.